The application of distributed leadership in middle school classroom - Ling, Xi; Bai, Yu Jie; Li, Bin Bin; Yang, Zhi (Frontiers in Education, 2023)
This mini-review explores the conceptual framework of distributed leadership and its application in middle school classrooms. Traditional teacher leadership in middle school classrooms has been found to be deficient in meeting the diverse needs of students. Therefore, this article investigates the potential advantages of distributed leadership in addressing the shortcomings of teacher leadership. The article examines the impact of distributed leadership on student achievement, particularly in promoting students' academic performance and ability. Through a critical analysis of existing literature, the review highlights the need to establish effective communication channels, teamwork, and trust in distributed leadership. Furthermore, the article acknowledges the limited empirical research on the effectiveness of distributed leadership in middle school classrooms. Despite this, the article concludes that the adoption of distributed leadership in middle school classrooms can improve student learning outcomes, classroom teaching effectiveness, and school operation efficiency. Overall, this conceptual exploration suggests that distributed leadership has the potential to offer a more effective and inclusive approach to leadership in middle school classrooms.